Dysregulation of EZH2/miR-138 axis contributes to drug resistance in multiple myeloma by downregulating RBPMS. Issue 11 (November 2018) - Rastgoo, Nasrin; Pourabdollah, Maryam; Abdi, Jahangir; Reece, Donna; Chang, Hong
Abstract EZH2 is highly expressed in multiple myeloma (MM). However, the molecular mechanisms underlying EZH2 overexpression and its role in drug resistance of MM remain undefined. Here we show that EZH2 is upregulated in drug-resistant MM cells and its aberrant overexpression is associated with poor prognosis of MM patients. Overexpression of EZH2 in parental MM cells renders them resistant to anti-myeloma drugs and suppression of EZH2 displays the opposite effects. Using miRNA target scan algorithms, we identify miR-138 as a regulator of EZH2, which is conversely repressed by EZH2-induced H3K27 trimethylation in MM-resistant cell lines and primary tumor cells. Analysis of ChIP-seq dataset and H3K27me3 ChIP reveals that RBPMS is a direct and functionally relevant target of EZH2. RBPMS silencing confers resistance to MM cells and restoration of RBPMS by miR-138 overexpression re-sensitizes the resistant cells to drug. Importantly, in vivo delivery of miR-138 mimics or pharmacological inhibitor of EZH2 in combination with a proteasome inhibitor, bortezomib, induces significant regression of tumors in xenograft model. This study establishes EZH2/miR-138 axis as a potential therapeutic target for MM.